Rapid preliminary screening of amine absorbents for post-combustion CO2 capture - Xi Tang; Bin Xu; Xiaoyi Gao; Xiaoshan Li; Ge Gao; Wen Chen; Fan Wu; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2026)

Novel dual-functional depressant for the selective depression behavior and mechanism of fluorite and calcite in bastnaesite flotation - Ruiqi Ge; Wenbao Liu; Yonglun Wang; Bohan Wang; Wengang Liu; Sikai Zhao; Cong Han; Yanbai Shen (Minerals Engineering, 2026)

Energy-efficient modulation of CO2 phase-change absorbents using tertiary amines: A comprehensive analysis combining experimental and mechanistic approaches - Ge Gao; Wenying Dong; Xuehao Li; Yansen Hu; Xiaoshan Li; Xi Tang; Wen Chen; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2026)

Combination of reduced fertilization and tobacco-maize rotation reshapes soil fungal community structure, functions, and ecological strategies - Cong Wang; Xiaomeng Wei; Tida Ge; Dan Chen; Julia Brandao Gontijo; Kaiyuan Gu; Yonglei Jiang; Weijun Shen; Jorge Luiz Mazza Rodrigues (Applied Soil Ecology, 2026)

Quality grading of raw goat milk and microbiota-driven quality degradation during storage at 4°C and 10°C - Mengyuan Cao; Min Li; Yizhuo Yan; Yifan Wu; Li Su; Jinghan Dai; Cong Wang; Xin Lv; Yan Zhang; Wupeng Ge; Baowei Yang (International Dairy Journal, 2026)

Injection timing optimization for low-carbon isopropanol–diesel blends in compression-ignition engines - Jun Cong Ge; Hongliang Luo; Ok Kyun Kim; Hae Woong Lim; Kihan Kwon (Fuel, 2026)

Full-range, high-sensitivity, and super-stretchable reduced silk fibroin/graphene oxide aerogels via a molecular interaction balancing strategy for multifunctional piezoresistive sensors - Yixuan Zhang; Hefeng Li; Cong Liu; Jiabao Zhu; Wenda Bai; Xianhua Huan; Siyi Tian; Lei Ge; Xiaolong Jia; Xiaoping Yang (Chemical Engineering Journal, 2026)

Regional flooding enhances N2O and CH4 emissions from agricultural fields: Evidence from a single extreme event across the North China Plain - Zhengkui Ge; Zhifeng Yan; Mike Peacock; Si-Liang Li; Xiaotang Ju; Pete Smith; Guirui Yu; Cong-Qiang Liu (Agricultural and Forest Meteorology, 2026)

Episodic tropical cyclones dominate cross-shelf sediment transport in the East China Sea - Shuai Cong; Xiao Wu; Jianzhong Ge; Yunhai Li; Naishuang Bi; Houjie Wang (Marine Geology, 2026)

A bioinspired chitosan-polymer facilitated CO2 utilization under mild reaction conditions - Linlin Li; Jiang Zhao; Qingmei Ge; Yin-Hui Huang; Hang Cong; Wenfeng Zhao (Biomass and Bioenergy, 2026)

Multi-media eDNA metabarcoding uncovers habitat-specific fish community and monitoring efficiency: implications for ecosystem management in a river–lake system (Honghu lake basin, China) - Ge Li; Borui Zou; Cong Wang; Lu Zhang; Xi Liu; Zhi Wang (Aquatic Sciences, 2026)

3D gravity and magnetic joint inversion based on a double branch multi-channel CNN - Wan-cong Jiang; Yong-hui Zhao; Jin-yao Gao; Shuang-cheng Ge; Zhi-fei Xie (Applied Geophysics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

NaOH regulation of steel slag carbonation: Interfacial activation and kinetic enhancement - Wenjing Tang; Jiale Tian; XinYu Zhu; Yu Cong Ge; Tao Wang; Zhenwei Yi; Mengxiang Fang; Kun Luo; Xiang Gao (Journal of Environmental Chemical Engineering, 2026)

Rapid and sensitive detection of feline herpesvirus-1 using fluorescent microspheres as labels for immunochromatographic test strips - Peipei Shao; Yuexiao Lian; Xiangnan Liu; Huizhen Liu; Jiantao Yu; Yongping Tang; Feng Cong; Ye Ge (Veterinary Research Communications, 2026)

Flexible SERS tape: A plasmonic hybrid of AuNPs and layered K2Ti8O17 nanowire network for on-site detection of pesticide residues - Lin Xu; Mingru Cui; Zhongqi Ge; Ruikang Zou; Cong Wang; Pengfei Ni; Xi Huang; Bo Zhong; Lijuan Wang (Analytica Chimica Acta, 2026)

Mamba-CrossAttention: Solving Flexible Job Shop Scheduling via sequence modeling and reinforcement learning - Zhi Cao; Cong Zhang; Yaoxin Wu; Yaqing Hou; Hongwei Ge (Swarm and Evolutionary Computation, 2026)

A cellulosic waste-upcycled 1T/2H-MoS2/biochar heterostructure for efficient cationic dye adsorption via a multi-anchor chemisorption mechanism - Yifan Lu; Min He; Mingna Ge; Luning Chen; Lin Han; Cong Tu; Bang Yuan; Jie Huang (Journal of Environmental Chemical Engineering, 2026)

Functional reorganization of microbial ecological clusters is associated with citrus soil health enhancement under greenhouse cultivation - Chenhong Liu; Qi Zhao; Lin Zhang; Fuzhi Ke; Xuebin Xu; Senxiang Yu; Jiaping Lang; Tida Ge; Cong Wang; Haoqing Zhang (Plant and Soil, 2026)

Environmental drivers and ecological processes underlying microbial community zonation in deep-sea polymetallic nodule sediments - Ning Guo; Wenquan Zhang; Tingting Li; Huameng Ge; Zepeng Zhang; Weizhe Li; Dewi Seswita Zilda; Ocky Karna Radjasa; Bailin Cong; Chengcheng Li; Shenghao Liu (Marine Environmental Research, 2026)

In-situ cultivation and process dynamics of algal-bacterial granular sludge in a continuous-flow self-circulation reactor - Wei-Kang Qi; Yu-Ge Sun; Ming-Ming Zhang; Rui Hu; Yong-Zhen Peng; Cong Wang (Bioresource Technology, 2026)

The law of oxidation and exothermic of low-rank coal at critical temperature: Based on the isothermal stage experiment method - Bing Lu; Xun Zhang; Ling Qiao; Cong Ding; Nan Fan; Ge Huang; Fengwei Dai (Fuel, 2026)

Distinct roles of nitrogen and phosphorus availability in preventing soil organic carbon loss in alfalfa-converted cropland - Xu-Long Zhang; Ge Li; Xiao-Peng Shi; Yang-Yang Zhao; Hai-Long Ma; Wen-Feng Cong; Fusuo Zhang; Feng-Min Li (Agriculture, Ecosystems & Environment, 2026)

Cyproflanilide, a novel meta-diamide insecticide, overcomes multiple insecticide resistance in Cnaphalocrocis medinalis: Evidence from comparative toxicity assays and genome-edited Drosophila - Wen-Chao Ge; Guang-Hang Chen; Bei-Bei Dong; Hong-Shuang Li; Meng-Zhen Wang; Feng-Xia Yang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Nondestructive assessment of refrigerated quality attributes of kiwifruit via hyperspectral imaging coupled with a point-to-interval prediction model - Sunli Cong; Jun Sun; Lei Shi; Chunxia Dai; Xiaohong Wu; Bing Zhang; Kunshan Yao; Xiao Ge (Food Chemistry, 2026)

Smart, tumor-targeted, and responsive intracellular delivery engineering (STRIDE) nanoplatform: co-delivery of siGLI1 and cisplatin prodrug to overcome lung adenocarcinoma chemoresistance - Ge Chen; Mengyang Liu; Yanan Sun; Shifei Zhang; Qingyi Liu; Yuxiang Liang; Kexin Cong; Meng Yan; Zhigan Zhang; Jinjiang Deng; Zongyu Wang; Ziqiang Li; et al. (Chemical Engineering Journal, 2026)

Targeting P2X7R Protects the Retina Against High-Altitude Hypoxia via NLRP3–Mediated Pyroptosis Suppression - Keke Ge; Yange Gu; Huan Xi; Siyuan Liu; Yatao Wang; Lu Yang; Cong Han; Xingxing Zheng; Hao Wang; Songjian Huang; Wenfang Zhang (Molecular Neurobiology, 2026)

Time-Resolved Oxidative Stress and Apoptosis in Murine Retina under Acute Hypobaric Hypoxia with Parallel Activation of the LIF–JAK–STAT3 Axis - Hao Wang; Qiang Ye; Songjian Huang; Keke Ge; Cong Han; Huan Xi; Junyi Qiao; Jingrong Feng; Peirun Wu; Yuhan Bao; Yi Yang; Wenfang Zhang (Molecular Neurobiology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Competent expression of effective and long-acting human α-Gal A-Fc fusion protein in the milk of transgenic mice - Mengke Yuan; Lan Yang; Chunyang Li; Zhiqiang Wu; Zhipeng Liu; Tianfei Du; Xinzong Rong; Cong Cong; Yongxia Zhang; Xiaoping Yu; Yali Gao; Zhengli Chen; et al. (Transgenic Research, 2025)

Corrosion risk and material degradation of copper-zinc alloys in aged biodiesel fuel systems - Jun Cong Ge; Hongliang Luo; Ik-Tae Im; Nag Jung Choi (Process Safety and Environmental Protection, 2025)

Impact of extreme storms on the effect of soil and water conservation measures - Ge Li; Jinfeng Wu; Zhentao Cong; Dawen Yang (Journal of Hydrology, 2025)

Corrigendum to “Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection” [J. Environ. Chem. Eng. 13 (5) (2025) 118803] - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yongwoo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yong-Woo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

Branched ligand-functionalized immuno-evasive PEGylation (BLIP) platform: Breaking through accelerated blood clearance and chemoresistance barriers with dual-targeting RNAi-chemotherapy synergy - Mengyang Liu; Ruijuan Xing; Ge Chen; Yuxiang Liang; Lu Huang; Yumeng Xi; Yue Li; Shifei Zhang; Yanan Sun; Yupin Song; Jintao Hao; Kexin Cong; et al. (Chemical Engineering Journal, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

Isolation and characterization of a marine strain: Bacillus inaquosorum, and its feeding effects on Sebastes schlegelii as feed additive - Xin-Kun Zhu; Ren-Ge Hu; Wei Cong; Yuan-Huan Kang; Li-Yan Wang; Tao Yang; Shu Li (Aquaculture, 2025)

Village ponds are hotspots of CO2 and CH4 emissions regulated by biological communities - Zhengkui Ge; Zhifeng Yan; Mike Peacock; Baoxuan Chang; Yunyun Zhang; Wenxin Wu; Si-Liang Li; David Bastviken; Cong-Qiang Liu (Environmental Pollution, 2025)

The SnRK1 kinase TaSnRK1.10 positively regulates heavy metal chromium tolerance mainly by mediating reactive oxygen species homeostasis and activating the phenylpropanoid biosynthetic pathway in wheat - Yihan Fu; Cong Chen; Pei Pei; Xiangyang Hao; Jiajia Jin; Shujie Shi; Qiang Ge; Pengfei Wang; Gezi Li; Guozhan Fu; Changqing Du; Guozhang Kang (Journal of Hazardous Materials, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

Mesua ferrea L. extract inhibits cell invasion and tumor growth in breast cancer in vitro and in vivo - Zhi-Ying Liu; Ge Ge; Shuang-Shuang Ma; Xi-Ya Chen; Yue Cong; Shu-Yun Wang; Ya-Ping Guo (Tissue and Cell, 2025)

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

The structure–activity relationship for CO2 absorption heat of chain diamines: Effects of amino types, methyl/ethyl groups, and chain lengths - Xi Tang; Ge Gao; Wufeng Jiang; Bin Xu; Fan Wu; Cong Luo; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2025)

Production and Subsequent Application of Different Biochar-based Organic Fertilizers to Enhance Vegetable Quality and Soil Carbon Stability - Jining Zhang; Li-ao Ge; Yuxiang Yang; Xianxian Zhang; Cong Wang; Huifeng Sun; Honghui Chen; Jian Huang; Sheng Zhou (Journal of Soil Science and Plant Nutrition, 2025)

Spatio-temporal scales of the Chinese Daqu microbiome: Heterogeneity, niche differentiation, and assembly mechanisms - Jie Tang; Junlin Wei; Yong Yang; Xiangyang Ge; Qiancheng Zuo; Cong Zhao; Yongguang Huang (Trends in Food Science & Technology, 2025)

Optimizing urban green space configurations for enhanced heat island mitigation: A geographically weighted machine learning approach - Yue Zhang; Jingtian Ge; Siyuan Wang; Cong Dong (Sustainable Cities and Society, 2025)

Bacterial community composition and metabolic characteristics of three representative marine areas in northern China - Huameng Ge; Chengcheng Li; Conghui Huang; Linlin Zhao; Bailin Cong; Shenghao Liu (Marine Environmental Research, 2025)

Photoelectrochemical water splitting improved by a cucurbit[7]uril-induced ternary heterojunction - Hong-Si Guo; Wenfeng Zhao; Qingmei Ge; Nan Jiang; Mao Liu; Hang Cong (Chemical Engineering Journal, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Phylogenomic analyses shed new light on the spatiotemporal evolution of global larches: Implications for the dynamics of boreal forests - Xiu-Fei Qiu; Yan-Yan Liu; Ge Wu; Cong-Hui Xu; Xin-Quan Liu; Xiao-Yan Xiang; Xiao-Xin Wei; Xiao-Quan Wang (Molecular Phylogenetics and Evolution, 2025)

Spatio-temporal coupling coordination analysis between local governments' environmental performance and listed companies' ESG performance - Xia Wu; Chunxu Hao; Yuhan Li; Chazhong Ge; Xianming Duan; Jing Ren; Cong Han (Environmental Impact Assessment Review, 2025)

A transformed Prussian blue analog as host of I2 for long-life aqueous zinc-iodine battery - Yang Qian; Ge Chang; Cong Huang; Yujie Yang; Yisu Hao; Qunli Tang; Aiping Hu; Yanhua Li; Xiaohua Chen (Chemical Engineering Journal, 2025)

Influence of energy-saving devices on the hydrodynamic characteristics of a waterjet-propelled ship: Experimental and numerical investigation - Kewei Song; Pei Xu; Jie Gong; Cong Sun; Shenwei Ge (Ocean Engineering, 2024)

Tripartite-motif 3 represses ovarian cancer progression by downregulating lactate dehydrogenase A and inhibiting AKT signaling - Yu Cong; Xin Cui; Yaqian Shi; Xinxing Pan; Ke Huang; Zhe Geng; Pengfei Xu; Lili Ge; Jin Zhu; Juan Xu; Xuemei Jia (Molecular and Cellular Biochemistry, 2024)

Unveiling the pathogenic and multidrug-resistant profiles of Vibrio alfacsensis: A potential identified threat in turbot (Scophthalmus maximus) aquaculture - Ren-Ge Hu; Lei Yang; Li-Yan Wang; Yu-Lin Yang; Hong-Jin Li; Bin-Tong Yang; Yuan-Huan Kang; Zhen-Lin Liang; Wei Cong (Journal of Hazardous Materials, 2024)

New insights into the functional group influence on CO2 absorption heat and CO2 equilibrium solubility by piperazine derivatives - Xi Tang; Bin Xu; Wufeng Jiang; Xiaoshan Li; Ge Gao; Fan Wu; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2024)

Gas-liquid interface derived lightweight and twistable BiOI/In2O3/tape assembly for photocatalytic NO removal - Liyang Zhang; Yangqin Gao; Ziyu Teng; Yida Liu; Xinming Liu; Chuanbo Cong; Kezhen Lai; Linping Li; Jipeng Dong; Ning Li; Lei Ge (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Large-scale production of a “skin-like” self-pumping fabric for personal sweat management - Meitong Ge; Fengxiang Chen; Chaoyu Chen; Honglian Cong; Zhijia Dong; Pibo Ma (Chemical Engineering Journal, 2024)

Comprehensive source identification of heavy metals in atmospheric particulate matter in a megacity: A case study of Hangzhou - Feili Li; Gaoxiang Zhang; Yifei Jinxu; Tianzheng Ding; Cong-Qiang Liu; Yunchao Lang; Nuohang Liu; Shuang Song; Yasheng Shi; Baozhu Ge (Journal of Environmental Management, 2024)

Conformational interlocking induced construction of hierarchically porous graphene membrane for ultrahigh-pressure sensing - Cong Liu; Hefeng Li; Jikang Zhao; Jiabao Zhu; Xianhua Huan; Yixuan Zhang; Ke Xu; Hongbo Geng; Xiaopeng Chen; Wenhui Ding; Lei Zu; Lei Ge; et al. (Chemical Engineering Journal, 2024)

CA1 Modulates the Osteogenic Differentiation of Dental Follicle Stem Cells by Activating the BMP Signaling Pathway In Vitro - Jin-ze Zhao; Ying-Ying Ge; Ling-fa Xue; Yao-xiang Xu; Jin Yue; Cong Li; Wen-lin Xiao (Tissue Engineering and Regenerative Medicine, 2024)

The evaluation of bacteriophage therapy in aquaculture: A systematic review and meta-analysis - Lei Yang; Qing Yang; Ren-Ge Hu; Wei Cong; Shu Li; Yuan-Huan Kang (Aquaculture, 2024)

Membraneless organelles assembled by AuNPs-enzyme integration in non-photosynthetic bacteria: Achieving high specificity and selectivity for solar hydrogen production - Hui Li; Xiaoxuan Yu; Yaqi Wu; Cong Li; Zhengwei Xu; Wang Liu; Shuheng Chen; Hongcheng Sun; Yan Ge; Zhenhui Qi; Junqiu Liu (Chemical Engineering Journal, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Water effect on CO2 absorption mechanism and phase change behavior in [N1111][Gly]/EtOH anhydrous biphasic absorbent: In density functional theory and molecular dynamics view - Wufeng Jiang; Ge Gao; Xiaoyi Gao; Bin Xu; Fan Wu; Xiaoshan Li; Liqi Zhang; Cong Luo (Chemical Engineering Journal, 2024)

Transcriptional and ultrastructural changes of macrophages after african swine fever virus infection - Cong Yuan; Yueyue Duan; Xiangtong Li; Yu Zhang; Liyan Cao; Tao Feng; Junwei Ge; Qi Wang; Haixue Zheng (Veterinary Microbiology, 2024)

Review of chemical looping technology for energy conservation and utilization: CO2 capture and energy cascade utilization - Jinbiao Yan; Sha Wang; Bin Hu; Huarong Zhang; Lipei Qiu; Weijun Liu; Yun Guo; Jun Shen; Bin Chen; Xiang Ge; Cong Shi (Journal of Environmental Chemical Engineering, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Pilot–scale vertical continuous–flow reactors applied to treat rural domestic wastewater at low temperature via aerobic granular sludge - Shibo Cong; Ge Yu; Shuai Xia; Haiyang Yu; Yang Sun; Yu Gao; Yuzhi Liu; Donglei Zou (Journal of Water Process Engineering, 2024)

Curcubit[8]uril-modulated asymmetric electroreductive hydrodimerization of coumarins with supramolecular encapsulation - Jie Liu; Qingmei Ge; Mao Liu; Hang Cong (Chemical Engineering Journal, 2024)

Review of waste plastics treatment and utilization: Efficient conversion and high value utilization - Bin Hu; Sha Wang; Jinbiao Yan; Huarong Zhang; Lipei Qiu; Weijun Liu; Yun Guo; Jun Shen; Bin Chen; Cong Shi; Xiang Ge (Process Safety and Environmental Protection, 2024)

Improvement of non-specific immunity, intestinal health and microbiota of crucian carp (Carassius auratus) juvenile with dietary supplementation of Bacillus coagulans BC1 - Ren-Ge Hu; Bin-Tong Yang; Zi-Yan Zheng; Zhen-Lin Liang; Yuan-Huan Kang; Wei Cong (Aquaculture, 2024)

Monoclonal Antibody Targeting CGRP Relieves Cisplatin-Induced Neuropathic Pain by Attenuating Neuroinflammation - Shun Xie; Zhenfang Gao; Jiale Zhang; Cong Xing; Yanxin Dong; Lanyin Wang; Zhiding Wang; Yuxiang Li; Ge Li; Gencheng Han; Taiqian Gong (Neurotoxicity Research, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

Reaction behaviors in pulverized coal MILD-oxy combustion affected by physical and chemical effects of diluents - Zhenghong Zhao; Zewu Zhang; Xiaojian Zha; Ge Gao; Fan Wu; Xiaoshan Li; Cong Luo; Liqi Zhang (Fuel, 2024)

Forebay entrainment risk effects on two fish species in the Williston Reservoir - Pengcheng Li; Yang Yang; Wenming Zhang; Nan Cong; Ge Yang; Weiwei Yao (Ecological Modelling, 2024)

Ship energy-saving device: Influence of the scale effect and hull roughness on the resistance reduction effect of an interceptor - Kewei Song; Jie Gong; Shenwei Ge; Cong Sun; Haiyan Yang; Weiping Zhang (Ocean Engineering, 2023)

Intermittent migration of mixing front driven by typhoon events on the inner shelf of the East China Sea: A FVCOM modeling study - Shuai Cong; Xiao Wu; Jianzhong Ge; Naishuang Bi; Yunhai Li; Jian Lu; Houjie Wang (Marine Geology, 2023)

Rapid oscillation of sediment transport between the Bohai Sea and the Yellow Sea induced by Typhoon Lekima (2019) - Yanhao Liu; Houjie Wang; Shuai Cong; Zhengchen Zang; Naishuang Bi; Changwei Bian; Jianzhong Ge; Xiao Wu (Marine Geology, 2023)

Construction of an ultra-stable mixed conductive layer to stabilize the solid-state electrolyte/Na interface by in-situ interface chemistry - Yujie Yang; Yisu Hao; Yan Zhang; Cong Huang; Bin Yao; Yang Qian; Ge Chang; Zhixiao Liu; Qunli Tang; Aiping Hu; Xiaohua Chen (Chemical Engineering Journal, 2023)

Application of calcium peroxide for efficient treatment of surface water turbidity: Mechanisms and microbial community responses - Zihang Ma; Zuhan Ge; Kexuan Liu; Cong Wang; Tao Wu; Jibiao Zhang (Journal of Environmental Chemical Engineering, 2023)

New insights into the structure-activity relationship for CO2 capture by tertiary amines from the experimental and quantum chemical calculation perspectives - Ge Gao; Bin Xu; Xiaoyi Gao; Wufeng Jiang; Zhenghong Zhao; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Chemical Engineering Journal, 2023)

The heterogeneity of microbial diversity and its drivers in two types of sediments from tidal flats in Beibu Gulf, China - Yong-Lian Ye; Kuo-Jian Ma; Yun-Han Fu; Zhi-Cheng Wu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Mudflats and sandflats are two common types of coastal tidal flats, the structure and function differences of microbial communities between them are still underappreciated. Beibu Gulf is a diurnal tidal regime located in China, the differences between the two type of tidal flats could be more distinct. In this study, we collected a total of 6 samples from Beibu Gulf, consisting of 3 sandflats samples and 3 mudflats samples, classified based on clay and silt content. Generally, the mudflats samples exhibited higher levels of NH 4 + _N and TOC, but lower in ORP and pH. The microbial diversity of the two types of tidal flats was investigated, revealing great differences existed and sandflats had higher microbial richness and diversity than mudflats. Furthermore, we analyzed the association between microbial communities and environmental factors, finding NH 4 + _N to have the highest contribution to the total variation in microbial community structure, and microbial groups such as Desulfobacterota, Campilobacterota, Chloroflexota, Calditrichota, Spirochaetota, Zixibacteria, Latescibacterota and Sva0485 group in mudflats were positively associated with NH 4 + _N. The functions of microbial community were predicted using metagenomic sequences and metagenome assembled genome (MAG). Mudflats contained more genes for carbon fixation. Nitrate and nitrite reduction were widely existed in mudflats and sandflats, but nitrogen fixation was only existed in mudflats, and Campilobacterota , Desulfobacterota and Gammaproteobacteria MAGs were mainly responsible for it. Sandflats composed more genes for ammonium oxidation, but no MAG was found whether in sandflats or mudflats. Microbes in mudflats exhibited a greater abundance of genes related to sulfur cycling, especially in reduction process, unique MAGs in mudflats such as Calditrichota, Chloroflexota, Desulfobacterota and Zixibacteria MAGs are responsible for sulfate and sulfite reduction. Finally, we predicted functions of ammonium related microbes in mudflats based on MAGs and found Campilobacterota and Desulfobacterota MAGs were important for high accumulation of ammonium in mudflats. This study illuminated the structural and functional differences of microbial communities in mudflats and sandflats, providing new insights into the relationship of microbial communities and environment in the tidal flat.

Involvement of the heat shock response (HSR) regulatory pathway in cadmium-elicited cerebral damage - Milton Talukder; Shao-Shuai Bi; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Genomic and phylotypic properties of three novel marine Bacteroidota from bare tidal flats reveal insights into their potential of polysaccharide metabolism - Kuo-Jian Ma; Yong-Lian Ye; Yun-Han Fu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Special geographical location and abundant organic matter profiles in tidal flats have resulted in great microbial diversity, in which Bacteroidota strains are considered as one of the primary degraders of polysaccharides, playing a crucial role in the carbon cycle. In this study, we collected sediment or sand samples from 34 bare tidal flats in China and investigated the profile of culturable bacteria, selected three Bacteroidota for polyphasic taxonomic analysis and revealed their polysaccharide metabolic potential. Totally, we isolated 352 pure cultured bacteria and they mainly distributed in Bacteroidota , Pseudomonadota , Bacillota , and Actinomycetota . It is shown that the bare tidal flats contained a large number of potential novel species, mainly distributed in Flavobacteriales and Cytophagales within Bacteroidota . Three Bacteroidota strains, M17 T , M82 T , and M415 T , isolated from mudflat were selected for polyphasic taxonomic analysis. The 16S rRNA gene sequence similarity between strain M17 T and Mangrovivirga cuniculi KCTC 72349 T was 99.28%, and less than 90.09% with other species; strain M82 T shared the highest 16S rRNA gene sequence similarity of 97.85% with Pontibacter litorisediminis KCTC 52252 T , and less than 97.43% with other species; strain M415T had higher 16S rRNA gene sequence similarities with type species of genera Eudoraea (92.62-93.68%), Zeaxanthinibacter (92.02-92.91%), and Muriicola (92.21-92.83%). Phylogenetic analysis based on 16S rRNA gene sequences and single-copy orthologous clusters showed that strains M17 T and M82 T represent novel species within the genus Mangrovivirga and Pontibacter , respectively, and strain M415 T represents a novel species of a novel genus within the family Flavobacteriaceae . The potential in polysaccharide metabolism of all these three strains was analyzed by genomes. The analysis revealed that glycoside hydrolases and glycosyltransferases account for more than 70% of the total CAZymes. Additionally, the numbers of polysaccharide utilization loci (PULs) and annotated CAZymes in Cytophagales spp. M17 T and M82 T were found to be higher than those in Flavobacteriales sp. M415 T . Highly specialized saccharolytic systems and the presence of numerous diversified CAZymes for obtaining energy through polysaccharide metabolism were speculated to help the three novel strains adapt to the utilization of both terrestrial and marine polysaccharides.

LncRNA SLC25A21-AS1 increases the chemosensitivity and inhibits the progression of ovarian cancer by upregulating the expression of KCNK4 - Ke Huang; Xiyi Chen; Zhe Geng; Xueyou Xiong; Yu Cong; Xinxing Pan; Siyu Liu; Lili Ge; Juan Xu; Xuemei Jia (Functional & Integrative Genomics, 2023)

Combustion behaviors of pulverized coal MILD-oxy combustion under different steam injection parameters - Zhenghong Zhao; Zewu Zhang; Xiaojian Zha; Ge Gao; Xiaoshan Li; Fan Wu; Cong Luo; Liqi Zhang (Fuel, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

A systematic review, meta-analysis and meta-regression of the global prevalence of foodborne Vibrio spp. infection in fishes: A persistent public health concern - Jun-Yang Ma; Xin-Kun Zhu; Ren-Ge Hu; Ze-Zheng Qi; Wen-Chao Sun; Zhi-Peng Hao; Wei Cong; Yuan-Huan Kang (Marine Pollution Bulletin, 2023)

Hyperforin: A natural lead compound with multiple pharmacological activities - Xin-Xin Li; Yu Yan; Jia Zhang; Kang Ding; Cong-Yuan Xia; Xue-Ge Pan; Yan-Jing Shi; Jie-Kun Xu; Jun He; Wei-Ku Zhang (Phytochemistry, 2023)

Bifunctional electrolyte additive with redox mediation and capacity contribution for sulfur cathode in aqueous Zn-S batteries - Ge Chang; Jilei Liu; Yisu Hao; Cong Huang; Yujie Yang; Yang Qian; Xiaohua Chen; Qunli Tang; Aiping Hu (Chemical Engineering Journal, 2023)

Fuel-NO formation mechanism in MILD-oxy combustion of CH4/NH3 fuel blend - Zhenghong Zhao; Zewu Zhang; Xiaojian Zha; Ge Gao; Wenchao Mao; Fan Wu; Xiaoshan Li; Cong Luo; Liqi Zhang (Fuel, 2023)

From multiple cropping frequency to multiple cropping system: A new perspective for the characterization of cropland use intensity - Ge Shen; Qiangyi Yu; Qingbo Zhou; Cong Wang; Wenbin Wu (Agricultural Systems, 2023)

Cerebellar injury induced by cadmium via disrupting the heat-shock response - Shao-Shuai Bi; Milton Talukder; Xue-Tong Sun; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2022)

Cadmium Through Disturbing MTF1-Mediated Metal Response Induced Cerebellar Injury - Shao-Shuai Bi; Milton Talukder; Hai-Tao Jin; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Neurotoxicity Research, 2022)

Aestuariibaculum sediminum sp. nov., a marine bacterium isolated from a tidal flat in Zhoushan - Zhi-Cheng Wu; Xin-Yin Zhang; Cong Sun; Lin Xu; Ge-Yi Fu; Xue-Wei Xu (Archives of Microbiology, 2021)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Improving the genome editing efficiency of CRISPR/Cas9 in Arabidopsis and Medicago truncatula - Tezera W. Wolabu; Jong-Jin Park; Miao Chen; Lili Cong; Yaxin Ge; Qingzhen Jiang; Smriti Debnath; Guangming Li; Jiangqi Wen; Zengyu Wang (Planta, 2020)
Main conclusion An improved CRISPR/Cas9 system with the Arabidopsis UBQ10 promoter-driven Cas9 exhibits consistently high mutation efficiency in Arabidopsis and M. truncatula. Abstract CRISPR/Cas9 is a powerful genome editing technology that has been applied in several crop species for trait improvement due to its simplicity, versatility, and specificity. However, the mutation efficiency of CRISPR/Cas9 in Arabidopsis and M. truncatula (Mt) is still challenging and inconsistent. To analyze the functionality of the CRISPR/Cas9 system in two model dicot species, four different promoter-driven Cas9 systems to target phytoene desaturase ( PDS ) genes were designed. Agrobacterium -mediated transformation was used for the delivery of constructed vectors to host plants. Phenotypic and genotypic analyses revealed that the Arabidopsis UBQ10 promoter-driven Cas9 significantly improves the mutation efficiency to 95% in Arabidopsis and 70% in M. truncatula. Moreover, the UBQ10-Cas9 system yielded 11% homozygous mutants in the T1 generation in Arabidopsis. Sequencing analyses of mutation events indicated that single-nucleotide insertions are the most frequent events in Arabidopsis, whereas multi-nucleotide deletions are dominant in bi-allelic and mono-allelic homozygous mutants in M. truncatula. Taken together, the UBQ10 promoter facilitates the best improvement in the CRISPR/Cas9 efficiency in PDS gene editing, followed by the EC1.2 promoter. Consistently, the improved UBQ10-Cas9 vector highly enhanced the mutation efficiency by four-fold over the commonly used 35S promoter in both dicot species.

An Interactive Integrated Interpretation of GPR and Rayleigh Wave Data Based on the Genetic Algorithm - Tan Qin; Yonghui Zhao; Shufan Hu; Cong An; Wenda Bi; Shuangcheng Ge; Lorenzo Capineri; Thomas Bohlen (Surveys in Geophysics, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Use of Tripterygium wilfordii Hook F for immune-mediated inflammatory diseases: progress and future prospects - Cong-ying Song; Ying-ge Xu; Yuan-qiang Lu (Journal of Zhejiang University-SCIENCE B, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Associations between ambient temperature and daily hospital admissions for rheumatic heart disease in Shanghai, China - Yihui Ge; Cong Liu; Yue Niu; Chen Chen; Weibing Wang; Zhijing Lin; Renjie Chen; Jing Cai; Haidong Kan (International Journal of Biometeorology, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

The impact of successive mass selection on population genetic structure in the Pacific oyster (Crassostrea gigas) revealed by microsatellite markers - Jingxiao Zhang; Qi Li; Qingzhi Wang; Rihao Cong; Jianlong Ge; Lingfeng Kong (Aquaculture International, 2018)

Picroside II Exerts a Neuroprotective Effect by Inhibiting mPTP Permeability and EndoG Release after Cerebral Ischemia/Reperfusion Injury in Rats - Shan Li; Tingting Wang; Li Zhai; Keli Ge; Jun Zhao; Weihong Cong; Yunliang Guo (Journal of Molecular Neuroscience, 2018)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

Review of arsenic speciation, toxicity and metabolism in microalgae - Ya Wang; Shu Wang; Pingping Xu; Cong Liu; Misha Liu; Yulan Wang; Changhai Wang; Chunhua Zhang; Ying Ge (Reviews in Environmental Science and Bio/Technology, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

A systematic proteomic analysis of NaCl-stressed germinating maize seeds - Ling-Bo Meng; Yi-Bo Chen; Tian-Cong Lu; Yue-Feng Wang; Chun-Rong Qian; Yang Yu; Xuan-Liang Ge; Xiao-Hui Li; Bai-Chen Wang (Molecular Biology Reports, 2014)

Isolation and characterization of fifteen polymorphic tetranucleotide microsatellite loci in Schizopygopsis younghusbandi Regan - Huan Zheng; Gui-Rong Zhang; Shan-Shan Guo; Kai-Jian Wei; Cong-Xin Xie; Tai-Ming Ge (Conservation Genetics Resources, 2013)

Determination of Endocrine Disrupting Chemicals in Surface Water and Industrial Wastewater from Beijing, China - Jing Ge; Jian Cong; Ying Sun; Guoxue Li; Zhiqiang Zhou; Chuanfan Qian; Fengmao Liu (Bulletin of Environmental Contamination and Toxicology, 2010)